Efektivitas Pemberian POC Urien Kelinci dan NPK Mutiara Terhadap Pertumbuhan dan Hasil Caisim (Brassica junces L.) Dalam Polybag - Romenti Luan, Maria; Sunaryo, Yacobus; Darnawi (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to determine the effect and interaction of lequid ferdilizer of fer rabbit urine and NPK inorganic fertilizer doses on the growth and yield of green mustard in polybags. This research was conducted on agricultural land in Rejowinangung village, Kotagede district, and Yoygakarta city. This research was conducted from November 2022 to December 2022. This study used 2 x 3 factorial experiment using a Completely Randomized Design (RAL). The first factor is the dose of NPK Mutiara fertilizer: NPK Mutiara dose K1: 0.10 gr/plant, K2: 0.18 gr/plant, and the second factor is the concentration of liquid organic fertilizer (CRD) rabbit urine: P1: 50 ml/plant, P2: 100 ml/plant, and P3: 150 ml/plant. The variables observed were plant height, number of leaves, leaf length, leaf width, stem diameter, plant fresh weight, and root/shoot ratio. Data analysis using multiple tests (ANOVA) and Ducan multiple range (DMRT) 5% The results show no interaction between the dose of NPK and the concentration of rabbit urine. At a concentration of 50 ml/liter of rabbit urine, treatment produced a better shoot ratio than concentrations of 100 ml/liter and 150 ml/liter. Concentrations of 100 ml/liter and 150 ml/liter gave results that were not significantly different in yield (fresh weight) plant. Similarly, the Dosing of NPK at 0.10 g/plant and 0.18 g/plant did not give significantly different of the results (fresh weight) of the plants.